Does Health Consciousness Matter to Adopt New Technology? An Integrated Model of UTAUT2 With SEM-fsQCA Approach - Mustafa, Sohaib; Zhang, Wen; Shehzad, Muhammad Usman; Anwar, Aliya; Rubakula, Gelas (Frontiers in Psychology, 2022)
Every emerging technology has its pros and cons; health-conscious users pay more importance to healthy and environment-friendly technologies. Based on the UTAUT2 model, we proposed a comprehensive novel model to study the factors influencing consumers' decision-making to adopt technology. Unlike prior studies that focused on linear models, this study used a Structural Equation Modeling- fuzzy set qualitative comparative analysis (SEM-fsQCA) approach to account for the complexity of customers' decision-making processes in adopting new technology. We collected, analyzed, and evaluated valid responses from 830 consumers using a deep learning SEM-fsQCA technique to capture symmetric and asymmetric relations. We have extensively incorporated a health-consciousness attitude as a predictor and mediator to understand better the decision-making towards technology adoption, specifically 5G technology. All the factors tested in our model are statistically significant except the economic factors. Health-consciousness attitude (HCA) and Behavioral intention (BI) found significant predictors and a valid mediator in the process of 5G technology adoption. FsQCA provided six configurations to achieve high 5G adoption. The findings have significant practical ramifications for telecom corporations, advertisers, government officials, and key policymakers. Additionally, the study added substantial theoretical literature to technology adoption, particularly the adoption of 5G technology.